Constipation and quality of life among non-academic staffs in school of health science, Universiti Sains Malaysia - Sonny, Damia Batrisyia Mohd (Universiti Sains Malaysia, 2023)
Constipation is a common medical problem among adult, which may have negative consequences on their lives and most people may suffer from constipation at some point in their lives. This study aims to assess the prevalence of constipation, the level of QOL, and its association between constipation and impact towards QOL, and association between socio-demographic factors and constipation among non-academic staffs. A cross-sectional study was conducted to recruit the respondent in School of Health Sciences, (SHS), Universiti Sains Malaysia (USM). A total of 78 non-academic staff aged between 18-65 ages years old under different programmes in SHS, that fulfilled inclusion criteria involved in this study. They were selected through simple random method using a set of set self-administered questionnaire. The data was analysed with Statistical Package for Social Science (SPSS) version 26.0 windows using descriptive analysis, independent T-test and Fisher Exact Test. Constipation was indicated in 44.5% respondents. The quality of life Highest Mean was found in Domain 3 (Social Domain) Mean=85.68, Only psychological domain had significant association with constipation, which is (p=0.15). Taken medication was the only significant factor associated to constipation (p=0.005). In conclusion, constipation is highly prevalent among non-academic staffs in SHS and there is need to focus preventive measures for constipation to avoid a more severe complication.